Intelligent and excellent: 2012 GCTAB board members’ conference & inaugural meeting of GCTI - Journal of Thoracic Disease, Editorial Team (Journal of Thoracic Disease, 2012)
On April 22, 2011, the Greater China Thoracoscopic Advisory Board (GCTAB) was officially established as medical science develops and minimally invasive surgery rapidly advances in China (Table 1). This gather-up of academic intelligences is a substantial step towards a more prefect standard for minimally invasive surgery. More patients would enjoy the benefits from the elevation in quality and ratio of minimally invasive thoracic surgery. Authoritative experts both from home and abroad converge on the GCTAB, including Profs. Jianxing He, Lunxu Liu, Qun Wang, Tianyou Wang, Yingkang Shi, Xiuyi Zhi, Wen Gao and Jun Wang. Gathering these intelligences, the GCTAB will establish and perfect the standards in minimally invasive thoracic surgery. The GCTAB also explores training models of thoracoscopic surgery and holds training on the basis of professional endoscopic education platforms of Johnson & Johnson. Its devotion in promoting minimally invasive thoracic surgery in China will provide safer procedures for patients with less injury.